Optimisation of protease purification from Christia vespertilionis leaves and its anti-inflammatory activity - Izzah Farhah Zambari,; Sitti Rahma Abdul Hafid,; Nur Airina Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Christia vespertilionis (L. f.) Bakh. f. is widely known for its anti-inflammatory and anti-cancer properties. However, there are no previous studies about extracting and purifying protease enzymes from C. vespertilionis leaves. Therefore, this study was conducted to extract and optimise the purification of protease from C. vespertilionis leaves and characterise its anti-inflammatory properties. The optimisation was performed using different levels of ammonium sulphate saturation (20, 40, 60, 80 and 100%). Next, dialysis was carried out for the sample with the highest specific activity (16.88 U/mg), achieved with 100% ammonium sulphate saturation. At 100% saturation, C. vespertilionis leaves showed an increase in the specific activity to 20.06 U/mg after dialysis. The findings demonstrate the successful extraction and purification of C. vespertilionis protease (CVP) with a molecular weight of 48 kDa, as proven by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. CVP also exhibited anti-inflammatory activity, with an inhibition of 45.6% in lipopolysaccharide (LPS)-stimulated RAW264.7 cells and IC50 of 19.24 μg/mL. The HPLC test further confirmed the presence of gallic acid and quercetin compounds in C. vespertilionis, which cure inflammation. The results indicate that optimised CVP purification was achieved and its anti-inflammatory ability was proven.